What Do Chemistry Teachers Say About Scientific Creativity and the Development of Rosella Flower Extract Indicators as a Learning Medium for Acid-Base Titration? - Meli Safitri; Noor Fadiawati; Chansyanah Diawati (Postgraduate, University of Mataram, 2024)
The rapid development of industry 4.0 makes scientific creativity an important skill for every individual to be able to adapt and develop. Therefore, in the learning process, it is necessary to provide for the development of students' scientific creativity both as a professional skill and as a general life competency. This research aims to describe teachers' perceptions of learning acid-base titration using natural indicators from Rosella Flower extract to increase students' scientific creativity. The research method used was a survey method by distributing questionnaires to 21 high school chemistry teachers throughout Bandar Lampung City. The results of the research show that 100% of teachers have never developed an acid-base titration indicator from Rosella flower extract, and trained students' scientific creativity by providing a real problem. Based on these findings, it can be concluded that it is necessary to develop natural indicators from Rosella Flower extract as a learning medium for acid-base titration to increase students' scientific creativity.